How price fairness and fit affect customer tariff evaluations. (2nd July 2018) - Leinsle, Philipp; Totzek, Dirk; Schumann, Jan Hendrik
Abstract : Purpose: Promotional cues related to notions of fair prices or pricing designed to fit consumers' needs are prevalent for many service offers. The purpose of this paper is to investigate how both customers' price fairness and idiosyncratic fit perceptions shape their tariff evaluations. Design/methodology/approach: Two experimental studies involving different tariff types and service contexts test the complex interplay of customers' perceived price fairness and idiosyncratic fit with customer and context characteristics on their tariff evaluations. Findings: Customers judge tariffs drawing on both the perceived price fairness and idiosyncratic fit, driven by the perceived price level of the tariff and the perceived pricing transparency of the firm. Customers' service usage and consumption goals moderate these effects: heavy users and hedonic consumers indicate lower price sensitivity while focusing more on their transparency perception. The role of perceived price fairness and idiosyncratic fit for tariff choice depends on the tariff/service context; idiosyncratic fit is important when it is incidental (e.g. flat rates) rather than intentional (i.e. customized tariffs) and when customers lack the expertise or confidence to evaluate price fairness such as in the case of relatively new services. Originality/value: Prior studies focused on either price fairness or idiosyncratic fit and thus cannot fully explain the complex interplay between both in the context of tariff choice. This paper explicates the conditions that affect the relative importance of both concepts and under which incidental offers are better received than premeditated ones.